The "Muhammad Curtain" of the Armenian Museum: A Unique Visualization of the "Oath of the Prophet"? - Movsesian, Atineh. (Tufts University. Tisch Library., 2022)
Armenian altar curtains have been (and are) used to conceal the altar during various stages of the liturgy. On a Sunday service, the curtain is closed for the priest and the deacons to complete the vesting ceremony; it opens for the Procession, and closes again for the preparation of the communion, and opens for the remainder of the service. During Lent, the curtain remains closed until Palm Sunday. Therefore, the curtains were often rich in decoration and Christian iconography.; The “Muhammad Curtain,” housed at the Armenian Museum of America in Watertown Massachusetts, in the Paul Bedoukian Collection, is a unique example of an Armenian altar curtain. The museum has dated the curtain to the seventeenth or eighteenth century and it is presumed to be from Iran or India. As an introduction of this interesting altar curtain, this paper aims to analyze its iconography, especially its unique depiction of the Prophet Muhammad, and encourage further research.; Why would an Armenian Christian altar curtain depict the Islamic Prophet? Christian Armenians and Muslims of Jerusalem have maintained cordial relations throughout history due to a decree issued by Prophet Muhammad confirming the rights of Armenian’s in Jerusalem. In 626 AD, Bishop Abraham I, the Armenian Patriarch of Jerusalem, along with many prominent Armenians went to the Holy Islamic city of Mecca to meet with the Prophet to secure their protection from the Islamic conquests. Therefore, I argue that this iconography, placed in the center of the altar curtain, is a visual representation of the promise of protection to the Armenians, and an important aspect that stimulates further understanding of the community for which it was made.; Poster presented at the Tufts Graduate Student Council's 27th Graduate Student Research Symposium, April 20, 2022.